Jurnal Penyuluhan: Manfaat Partisipasi Masyarakat dalam Program Pengelolaan Sampah - Adi Chandra Berampu, Ivanovich Agusta (PPs ILMU PENYULUHAN PEMBANGUNAN IPB, 2015)
The existence of the company in a public area should be able to bring benefits to society itself, as in the social, economic, and environmental. To realize these expectations then CSR programs are implemented by taking into account the participation of the community and other stakeholders, because participation is one of the the most important of community development principles.